Trust as a Mediator of the Effect of Live Streaming and Online Customer Review on Purchase Decision of Wardah Cosmetic Products Among TikTok Online Shopping Users in Surabaya - Dianty, Septy Ayu; Handayani, Wiwik; Hendrati, Ignatia Martha (Transpublika Publisher, 2025)
The swift rise of social commerce, notably TikTok Shop, has significantly altered how consumers shop for beauty products. This study analyzes the impact of live streaming and user reviews on the decision to buy Wardah products on TikTok Shop, with trust acting as a mediator. The research focused on Wardah customers in Surabaya who had used TikTok Shop for their purchases. Utilizing an accidental sampling technique, the study gathered responses from 105 participants. The data were processed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with SmartPLS 3.0 software. The findings demonstrate that live streaming significantly enhances both trust and purchase intentions. This pattern is mirrored for online customer reviews. Trust is also shown to be a significant direct predictor of purchase decisions. Finally, mediation analysis confirms that trust significantly mediates the paths through which live streaming and online reviews affect purchase decisions. This demonstrates that while live streaming and positive reviews directly encourage purchases, their effectiveness is substantially enhanced when they first establish consumer trust. For cosmetic brands on social commerce platforms, building trust is therefore a critical mechanism through which interactive marketing tools drive consumer decision-making.